National and Institutional Trends in Adverse Events Over Time: A Systematic Review and Meta-analysis of Longitudinal Retrospective Patient Record Review Studies. Issue 2 (30th March 2021) - Connolly, Warren; Li, Brian; Conroy, Ronan; Hickey, Anne; Williams, David J.; Rafter, Natasha
Abstract : Supplemental digital content is available in the text. Abstract : Objective: This study aimed to determine if the implementation of large-scale patient safety initiatives have been successful in reducing overall and preventable adverse event rates in hospital inpatients. Design: The design used in this study was systematic review and meta-analysis. Data Resources: We followed our published protocol (PROSPERO [CRD42019140058]) and searched the following databases: PubMed, CINAHL, PsycINFO, Cochrane Library, and Embase from inception to February 2020. The reference lists of eligible studies were also searched. Eligibility: All longitudinal retrospective record review studies that examined adverse event rates before and after the introduction of patient safety initiatives in hospital inpatients were included. Data Extraction: Data extraction, quality, and risk of bias assessment were carried out by 2 independent reviewers. Information on study design, setting, demographics, interventions, and safety outcome measures was extracted. Results: A total of 3894 articles were screened, and 7 articles met the eligibility criteria for our systematic review with 5 of these providing sufficient information for inclusion in the meta-analysis. The degree of heterogeneity was high among studies. The meta-analysis demonstrated a minimal risk reduction in overall adverse event rates of 0.017 (95% confidence interval, 0.002–0.032) when the lower-quality studies were excluded, with one adverse event being prevented for every 59 hospital admissions. Conclusions: These findings are significant when the large numbers of admissions to a hospital every year are considered. Given the low numbers of large-scale implementation studies, there is a need for more research on the effectiveness of patient safety initiatives to further assess the impact of such initiatives on adverse events.